Emergency Transport, Diagnosis and Resuscitation of Penetrating Injury Caused by Iron Rod: A Case Report - Shrestha, Jukel; Bastola, Hemanta; Koirala, Dinesh P; Shakya, Jasmine; Bom, Rabin; Maharjan, Ramesh K; Shakya, Yogendra M; Prasad, Pratap N (Journal of Institute of Medicine Nepal, 2021)
Foreign bodies with their long edges that penetrate the body are potentially life-threatening, owing to the resulting hemorrhagic shock and visceral damage. In an under-resourced environment, the outcome after major impalement injury can be improved by (a) rapid transport with the impaled object in situ (b) quick assessment and resuscitation in the emergency room (c) transport to operating room for definitive care. We report here the successful management of penetrating long iron rod injury from the perineum to the loin of pediatric patient, including transport from rural to tertiary hospital, diagnosis and, resuscitation.